Clima organizacional de la Constructora Perez Sandoval S.A - Ponce Perez, Paulina Pauleth (2021)
This case study is based on the problems presented in a company dedicated to meeting the needs of the banana sector and the general public, located in the Naranjal canton of the Guayas province, which in recent months has presented problems in which involves the entire work group that have severely impacted the harmonious operation of the company and interfered with the achievement of objectives. Through this study, it is expected to find the causes that caused the deterioration in labor relations, for which the work environment has become unsustainable and has led its Managers to make the decision to authorize this case study, due to the concern of the circumstances that have arisen in said facilities. In order to identify the causes, information methods, techniques and instruments will be used as detailed below; The inductive research method was applied, ideal for this case because it was able to investigate and obtain the necessary conclusions to determine exactly where the problem that originated the deterioration of the organizational climate in the company Construcciones Industriales e Civiles Pérez Sandoval SA began. The research used was accompanied by the survey and interview instruments, their application was made to the collaborators and the responses finally allowed the results to be quantified, analyzed and interpreted. It should be noted that the problems posed in the company are the responsibility of both the work team and the managers, their communication skills and interpersonal skills will define the continuous improvement of the company.